They snooze, you lose - Burmark, Lynell
In today's increasingly visual world, the art of giving presentations is a much-needed talent. They Snooze, You Lose, provides a comprehensive guide made especially for teachers and administrators who want to become presentation "stars" in their classrooms, at board meetings, or any time they are in front of an audience